TINGKAT KECEMASAN MAHASISWA DALAM MENGIKUTI PRAKTIK PENGALAMAN LAPANGAN BIMBINGAN KONSELING SEKOLAH (PPLBKS) TAHUN AKADEMIK 2012-2013 - Sari, Novita Ratna; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The problem in this study is the level of studentÂ anxiety in the following Praktek Pengalaman Lapangan Bimbingan dan Konseling SekolahÂ (PPLBKS) 2012-2013academicyear. Anxiety level of students in the following Praktek Pengalaman Lapangan Bimbingan dan Konseling Sekolah (PPLBKS) academic year 2012-2013 viewed from two aspects, namely in terms of the psychological aspects and physiological aspects (anxiety as physical symptoms, especially in the nervous system). This type of research is a descriptive study sought to describe a situation for what it is. The population in this study was students who follow the practice of field experience academic year 2012-2013. Sampling in this study using random sampling. The numbers are as many as 57 people. The instrument used in this study was a questionnaire. As for the use of data analysis techniques percentage. The results follow the anxiety level of students in the Praktek Pengalaman Lapangan Bimbingan dan Konseling Sekolah (PPLBKS) academic year 2012-2013 is seen from the psychological aspect of the criteria is very high (94.74%) and the physiological aspects of the criteria to be higher (57.89%). So the anxiety level of students in the following the Praktek Pengalaman Lapangan Bimbingan dan Konseling Sekolah (PPLBKS) 2012-2013 academic year are at very high category. Research students are advised to follow PPLBKS BK 2012-2013 academic year in order to relieve anxiety in one self in order for carrying out the practice field. Then also that during the performance of students PPLBKS not feel anxious and fearful during field training.